2004
DOI: 10.1179/016164104225016272
|View full text |Cite
|
Sign up to set email alerts
|

The nature and effects of cortical microvascular pathology in aging and Alzheimer's disease

Abstract: Age-related and amyloid-induced pathology of the cerebral microvasculature have been implicated as potential contributing factors to the pathogenesis of Alzheimer's disease (AD). The microvasculature plays a crucial role in maintaining brain homeostasis and deterioration of its integrity may have deleterious effects on brain function in AD, possibly leading to neurofibrillary degeneration, plaque formation, and cell loss. Brain vessels possess peculiar anatomical and physiological properties owing to their rol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
132
0
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 186 publications
(140 citation statements)
references
References 74 publications
5
132
0
1
Order By: Relevance
“…A variety of antigens expressed on either endothelial cells or the vascular basement membrane have been used including laminin (Eriksdotter-Nilsson et al, 1986), fibronectin (Krum et al, 1991), von Willebrand factor (Theilen et al, 1992), collagen IV (Gidday et al, 2005) and the heparin sulfate proteoglycan (HSPG) perlecan (Chen et al, 2005;Gidday et al, 2005;Bailey et al, 2004;Buée et al, 1994). All work well in embryonic or neonatal mouse and rat brain.…”
Section: Introductionmentioning
confidence: 99%
“…A variety of antigens expressed on either endothelial cells or the vascular basement membrane have been used including laminin (Eriksdotter-Nilsson et al, 1986), fibronectin (Krum et al, 1991), von Willebrand factor (Theilen et al, 1992), collagen IV (Gidday et al, 2005) and the heparin sulfate proteoglycan (HSPG) perlecan (Chen et al, 2005;Gidday et al, 2005;Bailey et al, 2004;Buée et al, 1994). All work well in embryonic or neonatal mouse and rat brain.…”
Section: Introductionmentioning
confidence: 99%
“…Dans les années 90, plusieurs altérations microvasculaires liées à l'âge (dépôts de collagène péri-vasculaires, atrophie de l'endothélium, épaississe-ment de la membrane basale, dégénérescence des pericytes, tortuosité des capillaires) ont été décrites au niveau ultrastructurel aussi bien dans le cerveau vieillissant que lors d'une MA (voir références [38][39][40][41]). En revanche, les analyses quantitatives des paramètres structuraux des capillaires cérébraux ont été rares et ont abouti à des résultats contradictoires.…”
Section: S C H W E I Z E R a R C H I V F ü R N E U R O L O G I E U N unclassified
“…Furthermore, the functional integrity of the brain microvascular network is crucial for the maintenance of energy metabolism and furnishing oxygen and nutrients to the brain parenchyma (Magistretti and Pellerin, 1999;Magistretti, 2000). Considering that the microvascular network can be severely altered in neurodegenerative disorders (Buée et al, 1994;Bailey et al, 2004), it becomes important to assess quantitatively and dynamically potential disease-or aging-related alterations in the brain microvascular bed in animal models. Recent technology permits in vitro and in vivo approaches to these issues (Nedergaard et al, 2003).…”
Section: Quantification Of 3d Spatial Complexity In Vascular Networkmentioning
confidence: 99%
“…Severe vascular modifications are also detected in several neurodegenerative disorders (Buée et al, 1994;Bailey et al, 2004). Electron microscopy studies have revealed thickening and vacuolization of the vascular basement membrane, thinning of microvessels referred to as atrophic or string vessels (Bell and Ball, 1981), increased tortuosity (Fischer et al, 1990), and fragmentation of the microvasculature related to a decrease in the number of long microvessels and their branches (Buée et al, 1994).…”
mentioning
confidence: 99%